2010
DOI: 10.1089/ars.2009.2977
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin Overexpression in Cultured Human Neuronal Cells Protects Against Hydrogen Peroxide InsultviaActivating Phosphoinositide-3 Kinase and Opening the Mitochondrial KATPChannel

Abstract: Cultured neurons tolerate low H(2)O(2) concentrations (< or =50 microM) through the activity of constitutive antioxidant response elements (ARE). At H(2)O(2) levels (> or =100 microM), neurons increase expression of the gene encoding for inducible hemoxygenase-1 while superoxide dismutase-2 and catalase remain unchanged. Despite this adaptive response, the endogenous antioxidant systems are overwhelmed, leading to decreased viability. Elevating the neuronal cell content of human neuroglobin (Ngb) prior to insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 64 publications
3
56
0
1
Order By: Relevance
“…However, Ngb directly activates the PI3K/AKT/mTOR (phosphatidylinositide 3-kinase/ AKT/ mammalian target of rapamycin) pathway of cell survival. 33 Furthermore, JNK may be involved in prooxidant pathways because the N-terminal Von Hippel-Lindau recognition site of hypoxia inducible factor-1a contains a JNK-binding domain. 34 Notably, translation to an in vivo stroke model confirmed that combined Ngb upregulation and JNK inhibition was better than single treatment using infarct size and neurologic deficit as outcome measures (Figures 4-6).…”
Section: Discussionmentioning
confidence: 99%
“…However, Ngb directly activates the PI3K/AKT/mTOR (phosphatidylinositide 3-kinase/ AKT/ mammalian target of rapamycin) pathway of cell survival. 33 Furthermore, JNK may be involved in prooxidant pathways because the N-terminal Von Hippel-Lindau recognition site of hypoxia inducible factor-1a contains a JNK-binding domain. 34 Notably, translation to an in vivo stroke model confirmed that combined Ngb upregulation and JNK inhibition was better than single treatment using infarct size and neurologic deficit as outcome measures (Figures 4-6).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also demonstrated that Ngb suppressed H 2 O 2 -induced Erk activation in HepG2 cells. These evidences support an important role of Ngb in oxidative stress, probably as an oxidative stress sensor or ROS scavenger (Herold et al, 2004;Brunori et al, 2005;Burmester and Hankeln, 2009;Antao et al, 2010). Oxidative stress is a critical mechanism in HCC genesis or development.…”
Section: Discussionmentioning
confidence: 53%
“…Neuroglobin (Ngb), a newly discovered intracellular respiratory globin with a hexa-coordinated heme (Burmester et al, 2000;Trent et al, 2001), plays an important role in protecting brain cells from ischemic (Sun et al, 2001;Chen et al, 2005b) or oxidative stress (Ye et al, 2009;Antao et al, 2010). Because Ngb shows a higher binding affinity to oxygen and nitric oxide (NO), it is hypothesized that the Ngb may function as the oxygen carrier, NO/ROS scavenger, or oxygen/ ROS sensor (Trent et al, 2001;Herold et al, 2004;Brunori et al, 2005;Burmester and Hankeln, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, in cultured cells, over expression of neuroglobin protects against amyloid beta, hydrogen peroxide, paraquat, and HA14-1 (a Bcl-2 inhibitor) induced cell death, as well as from oxygen and glucose deprivation (16)(17)(18)(19)(20)(21). In vitro, knockdown of endogenous neuroglobin renders cortical neurons more susceptible to hypoxia (16), and decreases viability of neuroblastoma cells under oxidative stress (22).…”
Section: Biological Effects Of Neruroglobinmentioning
confidence: 99%
“…Following the reduction of cytochrome c, the ferric form of neuroglobin also produced will bind to the G a subunit of the GPCR (6) inhibiting IP3 production (7) and so further suppressing potential calcium rise in the cytosol (45). The other product of the reaction of ferric neuroglobin with the GPCR namely the G bc subunit will then activate PI3K and Akt (21,66) leading to phosphorylation of 14-3-3 and hence suppression of the calcium-stimulated action of the Bcl-2 family protein Bad (8). Neuroglobin can also inhibit RacGTPase and Pak1 (9) preventing the rearrangement of the cytoskeleton necessary for the execution of apoptosis (67).…”
Section: Integration With Other Reported Intra-cellular Actionsmentioning
confidence: 99%